Phytoneering in clinical practice - Anton Iu. Tsukanov; Evgenii V. Matveev (ZAO "Consilium Medicum", 2021)
The discovery of antibiotics almost 100 years ago seemed to have forever solved the issue of treating infectious diseases for humanity. However, the avalanche-like growth in antibiotic resistance requires the search for alternative methods of treatment, one of which is treatment with herbal products created according to the phytoneering concept. It is a technology that combines the enormous potential of medicinal plants (phyto) with the knowledge and methodology of modern pharmaceutical research (engineering). The article presents 2 clinical cases of the use of the herbal product Canephron N for the prevention of cystitis and acute urolithiasis common disorders in the practice of a urologist.